Problems of Communication and Health Information for Elderly Women during the Covid-19 Pandemic: Case Study of Health Information Search for Elderly Women in Bandung - Prasanti, Ditha; Karimah, Kismiyati El (West Science Social and Humanities Studies, 2024)
Like mushrooms that grow in the rainy season, the health information that was scattered during the Covid-19 pandemic is also growing rapidly and going fast all the time. Transfer of health information about the Covid-19 case can be accessed easily by anyone and anywhere through digital media in their respective devices. Hoax in health information is not a strange thing anymore, so it is difficult to distinguish the truth from real information. This communication problem is being experienced by society, especially among elderly women in Bandung. This phenomenon has attracted the attention of the author to examine more deeply with the following research objectives: 1) knowing the process of seeking health information for elderly women during the Covid-19 pandemic in Bandung; 2) knowing the reasons for the communication process and the selection of media and health information used by these elderly women. In this case, the uniqueness of the research lies in the research subject, where the category of elderly women with various physical and mental health conditions they experience must face exposure to health information during the Covid-19 pandemic. This study uses a case study method by interviewing 5 selected informants in this research. The results of the research were found to contribute thoughts in the study of health communication in the digital era that occurred during the Covid-19 pandemic. The findings of this study include the following, (1) the process of searching for health information carried out by informants during the Covid-19 pandemic is unique because it varies through word of mouth and digital media, with information content about various herbal / traditional treatments; (2) the reason for the search for health information is an effort to contain the spread of covid-19, a form of self-awareness and to prevent exposure to covid-19.